Management of medullary carcinoma of the thyroid: a review. Issue 7 (July 2022) - Jayasinghe, Ravindri; Basnayake, Oshan; Jayarajah, Umesh; Seneviratne, Sanjeewa
Medullary thyroid carcinoma (MTC) is an uncommon malignancy of neuroendocrine origin derived from the parafollicular C cells. Although infrequent, the interest in this cancer exceeds its incidence owing to its distinctive features and its characteristic association with other endocrine tumors. Although the majority of MTCs are sporadic, hereditary varieties occur in isolation or as a part of multiple endocrine neoplasia type 2 syndrome (MEN 2). Currently, complete surgical resection of the tumor and nodal metastases with a curative intent remains the mainstay of therapy. The role of adjuvant therapy is limited, although radiotherapy and newer targeted therapies are routinely used for metastatic disease. The lack of consensus in the available guidance regarding the most appropriate diagnostic, therapeutic and follow-up strategies has caused substantial variability in clinical practice. Therefore, this review summarizes the latest available evidence and guidelines on the management of MTC with an emphasis on diagnosis, surgical treatment and follow-up.